PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BRAILLE SUBPOKOK BAHASAN PERSEGI PANJANG DAN PERSEGI KELAS VII SMPLB-A (TUNANETRA) - Dimas, D; Susanto, S; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2015)
Abstract. One of compulsory subject taught in SMPLB-A is mathematic. Geometry is known as part of mathematic. SMPLB-A student also learn rectangle and square but there is only few media and worksheet that can make them learn independently. This research is developing a worksheet based on four-D models. The developed Braille worksheet have to satisfy validation criteria, effectiveness criteria and practicality criteria. After analize data from research process, obtained that validation average value (Va) is 3,77 which means this Braille worksheet is valid. The effectiveness criteria is obtained from student’s and teacher’s activity which indicate that the activity is satisfy ideal time, so the Braille worksheet is effective. For practicality criteria, we use questionnaire to student. From the questionnaire, value percentage reach 86,25% which indicates that the Braille worksheet at good category and satisfy the practicality criteria. After Braille worksheet fullfill the validation, practicality and efectifeness criteria, this worksheet can be disseminated to school. Key Words: blind student, Braille worksheet, 4-D models.